Rice Farming Technology Adoption: A Gender Perspective on Technology Acceptance Model - Victor S. Rosales; John Alan D. Lee; Michelle Samantha M. Gutierrez; John G. Adil, Jr.; Glay Vhincent C. Sumaylo (Journal of Technical Education and Training, 2024)
Rice farming technologies are revolutionizing agriculture by enhancing productivity, financial efficiency, sustainability, and livelihoods. This study examines demographic characteristics and technology adoption patterns among male and female rice farmers in Misamis Oriental and Lanao del Norte, Northern Mindanao, Philippines, highlighting prevalent machinery and practices used. A survey of 286 farmers (156 males and 130 females) provided insights into backgrounds, technology utilization, and perceptions. Results indicate that while male farmers are the majority, female farmers tend to be older. Most farmers have a high school education and are members of farmers’ associations. Both genders adopt a range of rice farming machinery, including mud boats, turtles, and harvesters, though ownership is limited across genders. Using TAM, the study evaluates how well the farmers perceive technology acceptance by examining perceived ease of use, usefulness, and attitude towards use. Structural Equation Modelling (SEM) analysis indicates significant links between these constructs and suggests that farmer perception substantially affects the adoption of rice farming technology. The research concludes that gender as a variable also moderates technology acceptance and use, although it seems that gender does not have a significant impact on the overall attitudes towards adoption, which points out the differences in needs and views for male and female farmers. Such evidence would mean that there is a difference between men and women in the adoption of rice farming technology. The research adds to the knowledge of the determinants of technology acceptance in agriculture and highlights the need for gender-based policies and programs. Considering such needs of men and women farmers can assist policymakers in increasing the adoption of technology and in the development of agriculture in a more gender-equitable way.